Loss of stromal caveolin-1 expression: a novel tumor microenvironment biomarker that can predict poor clinical outcomes for pancreatic cancer. - Tao Shan (Public Library of Science (PLoS), 2014)
Aims Cancer development and progression is not only associated with the tumor cell proliferation but also depends on the interaction between tumor cells and the stromal microenvironment. A new understanding of the role of the tumor microenvironment suggests that the loss of stromal caveolin-1 (Cav-1) as a key regulator may become a potential therapy target. This study aims to elucidate whether stromal Cav-1 expression in pancreatic cancer can be a strong prognosis biomarker. Methods Tissue samples from 45 pancreatic cancer patients were studied. Parenchyma and stroma were separated and purified using laser capture microdissection. Stromal Cav-1 expression was measured from pancreatic cancer, paraneoplastic, and normal tissue using immunohistochemistry. We analyzed the correlation of stromal Cav-1 expression with clinicopathologic features and prognostic indicators, such as tumor marker HER-2/neu gene. Results Specimens from six patients (13.3%) showed high levels of stromal Cav-1 staining, those from eight patients (17.8%) showed a lower, intermediate level of staining, whereas those from 31 patients (68.9%) showed an absence of staining. Cav-1 expression in cancer-associated fibroblasts was lower than that in paracancer-associated and in normal fibroblasts. Stromal Cav-1 loss was associated with TNM stage (P = 0.018), lymph node metastasis (P = 0.014), distant metastasis (P = 0.027), and HER-2/neu amplification (P = 0.007). The relationships of age, sex, histological grade, and tumor size with stromal Cav-1 expression were not significant (P>0.05). A negative correlation was found between circulating tumor cells and stromal Cav-1 expression (P<0.05). Conclusion The loss of stromal Cav-1 in pancreatic cancer was an independent prognostic indicator, thus suggesting that stromal Cav-1 may be an effective therapeutic target for patients with pancreatic cancer.